2015
DOI: 10.1097/md.0000000000001027
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Simple Bone Cyst Using a Cannulated Hydroxyapatite Pin

Abstract: Simple bone cysts (SBCs) are benign bone tumors. However, the treatment of SBCs remains controversial because of their healing rate and the invasiveness of surgery. The purpose of the present study was to evaluate the treatment of SBCs using a cannulated hydroxyapatite (HA) pin.A total of 43 patients (35 males, 8 females; mean age 12.1 years; age range, 5–22 years) with SBCs were treated with continuous decompression by inserting ceramic HA pins between 1989 and 2014. The SBCs were located in the calcaneus in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Those aggressive operations are extensive and complex, often with high complications [12]. In recent decades, new treatments have been developed, such as intralesional injections of steroids [13,14], intralesional injections of bone marrow [15], bone grafting with homologous cancellous bone chips [16], bone grafting with freeze-dried crushed cortical bone [17], and decompression with screws or pins with holes [18]. Even though these new surgical treatments present promising short-term outcomes, most of them are likely to end up with partial recoveries [19], and the recrudesce and tenacity are still the biggest challenges [3].…”
Section: Introductionmentioning
confidence: 99%
“…Those aggressive operations are extensive and complex, often with high complications [12]. In recent decades, new treatments have been developed, such as intralesional injections of steroids [13,14], intralesional injections of bone marrow [15], bone grafting with homologous cancellous bone chips [16], bone grafting with freeze-dried crushed cortical bone [17], and decompression with screws or pins with holes [18]. Even though these new surgical treatments present promising short-term outcomes, most of them are likely to end up with partial recoveries [19], and the recrudesce and tenacity are still the biggest challenges [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a significantly higher recurrence rate was found for patients with a lesion contacting the physis [16]. However, the other studies demonstrated that the results of PSI might be worse in as many as half of the patients had the lesion relapses [26]. In addition, despite its anti-inflammatory properties, extra care should be taken when administering steroid injection, due to its possible adverse effect [27][28][29][30].…”
Section: Discussionmentioning
confidence: 65%
“…Alternative treatment options were reviewed with the family. These included cyst injection with or without supplemental fixation [3,7,8]. The risks and benefits were discussed with the family, including the potential need to cross the proximal femoral growth plate with fixation which may lead to growth arrest [7].…”
Section: Case Presentationmentioning
confidence: 99%